HUBUNGAN ANTARA TUAN DAN HAMBA DALAM DUNIA KERJA BERDASARKAN KOLOSE 3:22-4:1 - Pestaman Siagian; Malik Malik (Phronesis: Jurnal Teologi dan Misi, 2023)
In Indonesia, the relationship between workers and employers is regulated in a legal regulation that aims to balance interests and justice. However, many disputes between workers and employers are caused by unequal interests and injustice. A more appropriate relationship is needed to ensure fairness and, at the same time, be able to encourage workers and employers to give their best in their relationships. This paper seeks to provide an alternative relationship between workers and employers to ensure justice and provide the best for workers and employers who depart from the spirit of serving and are centred on Christ. This paper is qualitative research that offers a model of servant relations obtained through the excavation of Colossians 3: 22 – 4:1 with the exegesis method. This paper concludes that the servant relationship between workers and employers centred on Christ, with the motive of serving each other based on the values ​​given by Colossians 3: 22 – 4: 1. This awareness will undoubtedly encourage workers and employers to give their best.